2006
DOI: 10.1111/j.1745-7262.2006.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of vitamin E against oxidative damage caused by formaldehyde in the testes of adult rats

Abstract: FA destroys the testicular structure and function in adult rats by inducing oxidative stress, and this damage could be partially reversed by VE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
97
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 14 publications
18
97
1
Order By: Relevance
“…In addition, excessive ROS increases germ cell apoptosis and inhibits the activity of spermatozoa [Fujii et al 2003]. Similar phenomena are often observed after exposure to other chemicals that cause testicular damage [Aly et al 2009;Zhou et al 2006a;Zhou et al 2006b;Doreswamy et al 2004]. It suggests that oxidative stress is one of the important mechanisms of testicular damage.…”
Section: Dbp Induces Testicular Oxidative Damagementioning
confidence: 89%
See 1 more Smart Citation
“…In addition, excessive ROS increases germ cell apoptosis and inhibits the activity of spermatozoa [Fujii et al 2003]. Similar phenomena are often observed after exposure to other chemicals that cause testicular damage [Aly et al 2009;Zhou et al 2006a;Zhou et al 2006b;Doreswamy et al 2004]. It suggests that oxidative stress is one of the important mechanisms of testicular damage.…”
Section: Dbp Induces Testicular Oxidative Damagementioning
confidence: 89%
“…Environmental contaminants have been shown to induce ROS generation in both intra-and extracellular spaces of cells or individuals leading to cell death and tissue injury [Abdulwahid Arif and Ahmad Khan 2010;Aly et al 2009]. Previous studies from our laboratory have also shown that environmental factors alter the pro-oxidant and antioxidant balance in testis [Zhou et al 2006a;2006b].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E has also been shown to suppress lipid peroxidation in testicular microsomes and mitochondria 36,37 and to reverse the detrimental effects of oxidative stress on testicular function mediated by exposure to such factors as ozone, iron overload, intensive exercise or exposure to aflatoxin, PCB, cyclophosphamide and formaldehyde. 28,32,33,[38][39][40][41][42] Furthermore testicular vitamin E levels have also been shown to fall significantly when oxidative stress is induced by exposure to pro-oxidant stimuli such as chromium. 34 Although catalase is of limited importance in the testes, there are several isoforms of GPx in this tissue that use glutathione (GSH) as a source of electrons to reduce H 2 O 2 to water.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…Various animal studies showed that HCHO exposure generated reactive oxygen species (ROS) by disrupting the balance between oxidants and antioxidants in various tissues (Teng et al 2001;Gurel et al 2005;Saito et al 2005;Zhou et al 2006) and resulted in oxidative DNA damage (Sul et al 2007). The formation of ROS leads to single-and double-strand breaks in DNA and modifications of purine and pyrimidine bases, as well as modification to 2 -deoxyribose (Powell et al 2005).…”
mentioning
confidence: 99%